الشّكوى في شعر أسامة بن منقذ - تريعة, أشواق (جامعة الوادي - University of Eloued, 2019)
تسعى هذه الدراسة للكشف عن ظاهرة الشكوى باعتبارها ظاهرة اتسم بها شعر "أسامة بن منقذ "، متخذين ديوانه أنموذجًا للدراسة ومحاولين الوقوف على مفهوم الشكوى ، ثم استجلاء مظاهرها وصورها وموضوعاتها في الديوان ومدى مساهمتها في تكثيف الدّفقة الشعرية ورصف النّص الشعري وشحنه بمختلف الجماليات الأدبية، وبالتالي سنحاول إنقاذ الشاعر من بوتقةِ النّسيانِ وسننفضُ عنه غبار الإهمال . الكلمات المفتاحية: الشّكوى؛ الشاعر؛ أسامة بن منقذ؛ ظاهرة؛ تجليات. : Abstract This study seeks to detect the phenomenon of complaint in the poetry of "Oussama Iben Mounketh",taking his volume as a model of the study . The researchers thereby tries to stand on the concept of complaint in term of language and terminology and then clarify their manifestations and images and themes in this volume of poetry and the extent of their contribution to intensify.its poetic splash and ornament . the poetic text with different Literary aesthetics , so we as will try to save the poetry from the oblivion crucible .Keywords: complaint, poetry, Oussama Iben Mounketh, phenomenon, manifestations
مقال
Keywords: الشاعر- أسامة بن منقذ - ظاهرة- تجليات